Struktur Modal, Leverage, CSR Disclosure, Nilai Perusahaan, dan Perusahaan Sub Sektor Farmasi - Pradnyawati, Sintya; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2024)
Firm value is the investor's perception of the company's level of success to be able to provide maximum shareholder prosperity by increasing the company's share price. Purpose of this study was to obtain empirical evidence regarding the effect of capital structure, leverage, and corporate social responsibility disclosure on firm value. This study took samples from the pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2017-2019. Sampling technique used was purposive sampling, 10 companies were obtained with 30 observations. Analyzed using multiple linear regression analysis. Based on the results, capital structure, leverage, and corporate social responsibility disclosure have a positive effect on firm value. This shows that the level of capital structure, leverage and corporate social responsibility disclosure can increase firm value. Keywords: Capital Structure; Leverage; Corporate Social Responsibility Disclosure; Firm Value.